Control fruit fly for profitable sweet gourd production (Progressive Agriculture, 2019)
A field experiment was conducted in the farmer’s field at Salaipur, Mithapukur, OFRD, Rangpur during 2015-2016 to control cucurbit fruit fly effectively through the use of sex pheromone trap. The trial was conducted among six farmers. Three treatments viz., T1 (Sex pheromone+Poison bait+Sanitation (9 spot)), T2 (Sex pheromone+Poison bait+Sanitation (16 spot)) and T3 (Farmers practice) were compared. The total land area was 7200m2. The higher fruit yield (25.86 t/ha) was obtained from T2 (Sex pheromone+Poison bait+Sanitation (16 spot). The lower fruit yield (21.43 t/ha) was obtained from T3. The gross margin (Tk.96375/ha) and BCR (3.92) was also higher with the use of T2 (Sex pheromone+Poison bait+Sanitation (16 spot). The findings related to control of fruit fly of sweet gourd will be an important role in pest management safely and it will be play important for farmer’s profitability.Progressive Agriculture 30 (2): 173-178, 2019